Sucking habits in childhood and the effects on the primary dentition: findings of the Avon Longitudinal Study of Pregnancy and Childhood - KAREN DUNCAN, CLARE MCNAMARA, ANTHONY J. IRELAND, & JONATHAN R. SANDY (IAPD and Blackwell, 2008)
The prevalence of non-nutritive sucking habits in children has been estimated to be between 61% and 90%.